Salinity effect on growth of three dinoflagelltaes, protoceratium reticulatum, alexandrium tamiyavanichii and alexandrium tamutum - Nurul Zainab, Binti Along (Universiti Malaysia Sarawak, UNIMAS, 2012)
Dinoflagellate Protoceratium reticulatum, Alexandrium tamiyavanichii and Alexandrium tamutum are among the toxic and non-toxic dinoflagellate species found recently in Malaysian waters. To determine the salinity tolerance and growth of dinoflagellate species, study was carried out using clonal cultures available at UNIMAS cultures collection. Cultures were maintained in ES-DK medium under a light intensity of 140 µmol m-2s -1 and 12:12 hour light:dark photoperiod. Natural seawater had been used as the medium base. Salinities variation were 5, 10, 15, 20, 25 and 30 psu. The cell counting was carried out under a light microscope approximately every two to three days. Mean cell diameter and cell volume were taken and calculated. P. reticulatum salinity tolerance was between 30-10 psu, A. tamutum between 30-15 psu and A. tamiyavanichii between 30-20 psu. P. reticulatum, A. tamutum were categorised as euryhaline species, while A. tamiyavanichii as a stenohaline species. Cell volume was decreasing as salinities concentration increasing. Salinity tolerance in decreasing order A. tamiyavanichii < A. tamutum < P. reticulatum.